Effect of Substrate Use on Fish Welfare Level of Goldfish (Carrasius auratus) - Helmi Hirman Anugrah; Robin; Arif Supendi (CV Edujavare Publishing, 2026)
Goldfish (Carassius auratus) is a freshwater ornamental fish with high economic value and is widely kept in aquariums. Fish welfare is an important aspect in its maintenance because it affects the growth, color, behavior, and environmental conditions of the fish. This study aims to assess the effectiveness of using different substrates on the level of fish welfare of goldfish. The study was conducted for 14 days using a Completely Randomized Design (CRD) with three treatments: aquatic plant (Hydrilla verticillata) substrate, zeolite substrate, and no substrate, each with three replications. The parameters observed included growth in length, color changes, behavior, and water quality consisting of temperature, pH, and dissolved oxygen (DO). The results showed that the use of aquatic plants gave the best results compared to other treatments. The growth in length of fish in the aquatic plant treatment reached an average of 2.06 cm, higher than the zeolite (1.46 cm) and no substrate (1.13 cm). The highest increase in fish color was also observed in the aquatic plant treatment with an average score of 24, compared to zeolite (20) and without substrate (16). The ANOVA test results showed that the substrate treatment had a significant effect on length growth (P = 0.0042) and changes in fish color (P = 0.000204). In addition, the aquatic plant treatment resulted in more stable water quality with temperature, pH, and DO within the optimal range and showed more active and normal fish behavior. Thus, the use of aquatic plants (Hydrilla verticillata) as a substrate was proven to be more effective in improving fish welfare of goldfish compared to zeolite or without substrate.